New phases and solid solutions in the systems PbO-Bi2O3-P2O5/As2O5/V2O5a) - Jie, Yucheng; Eysel, Walter (Powder diffraction, 1995)
The systems PbO-Bi2O3-P2O5/As2O5/V2O5 have been studied with respect to their compounds and solid solutions. A number of new compounds, particularly with high-Bi contents were found. Most of them are structurally closely related to the CaF2 and δ-Bi2O3 structures. Several binary and ternary solid solutions with P/As/V substitutions were investigated.